2017
DOI: 10.1002/eji.201746987
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐142 controls thymocyte proliferation

Abstract: T-cell development is a spatially and temporally regulated process, orchestrated by well-defined contributions of transcription factors and cytokines. Here, we identify the noncoding RNA miR-142 as an additional regulatory layer within murine thymocyte development and proliferation. MiR-142 deficiency impairs the expression of cell cycle-promoting genes in mature mouse thymocytes and early progenitors, accompanied with increased levels of cyclin-dependent kinase inhibitor 1B (Cdkn1b, also known as p27 ). By us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…Conversely, other miRNAs boost the immune response. For instance, miR-142-deficient mouse T cells showed reduced proliferation, deregulated cytokine expression and decreased secretion of pro-inflammatory cytokines such as IFN-γ, IL-17, and IL2 in response to activation ( 32 , 33 ). Other examples of enhancer miRNAs are miR-155 and miR-17~92; miR-155-depleted mice are immunodeficient ( 34 ), whereas miR-17~92-deficient T cells exhibited reduced antitumoral responses ( 35 ).…”
Section: Lessons From Mirna-deficient Modelsmentioning
confidence: 99%
“…Conversely, other miRNAs boost the immune response. For instance, miR-142-deficient mouse T cells showed reduced proliferation, deregulated cytokine expression and decreased secretion of pro-inflammatory cytokines such as IFN-γ, IL-17, and IL2 in response to activation ( 32 , 33 ). Other examples of enhancer miRNAs are miR-155 and miR-17~92; miR-155-depleted mice are immunodeficient ( 34 ), whereas miR-17~92-deficient T cells exhibited reduced antitumoral responses ( 35 ).…”
Section: Lessons From Mirna-deficient Modelsmentioning
confidence: 99%
“…For instance, some, but not all, functions of miR-155 in the immune system could be ascribed to its repression of Socs-1 ( 47 ). On the other hand, targeted deletion of a miR-142-binding site in Cdkn1b did not phenocopy aberrant proliferation of thymocytes observed in miR-142-deficient mice ( 48 ).…”
Section: Micrornas (Mirnas) Controlling T-cell Development and Functimentioning
confidence: 91%
“…A cluster of six related miRNAs, miR-17–92, confers competitive fitness to the earliest T-cell progenitors in the thymus and pre-thymic progenitors by regulating IL-7 receptor levels and IL-7 signaling ( 85 ). Conversely, miR-142 curtails numbers of early T-lineage progenitors, although loss of this miRNA inhibits proliferation and ultimately results in peripheral lymphopenia ( 48 ). Together, miR-17–92 and miR-142 help to explain the majority of T-lineage developmental defects observed upon early depletion of all miRNAs.…”
Section: Micrornas (Mirnas) Controlling T-cell Development and Functimentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, miR-142 is an evolutionarily conserved miRNA that can be selectively expressed in hematopoietic tissue. Mildner et al [44] showed that the deletion of miR-142 could affect cell homeostasis. Their further analysis revealed that miR-142 was required for thymocyte precursor development and T-cell maturation.…”
Section: Mirnas and T-cell Developmentmentioning
confidence: 99%